PROS1‐MERTK Axis Drives Tumor Microenvironment Crosstalk and Progression in Papillary Thyroid Microcarcinoma - Wenqian Zhang; Ye Zhang; Zhu Liu; Zhiyuan Wang; Huaqin Wang; Xiaoyu Ji; Hongyue Su; Fan Yang; Lirong Yan; Ying Xu; Hao Zhang; Wei Sun (Advanced Science)
Abstract The incidence of papillary thyroid carcinoma (PTC) has been rising annually, with papillary thyroid microcarcinoma (PTMC) accounting for more than half of the cases. While most PTMCs exhibit indolent growth and a favorable prognosis, some undergo clinical progression with poor outcomes. Thus, identifying biomarkers associated with PTC, particularly those related to PTMC progression, is crucial for precise risk stratification and treatment planning. This study utilized single‐cell RNA sequencing on 19 surgical tissue specimens from 15 patients, including four para‐tumor tissues, four non‐progressive PTMCs, five progressive PTMCs, and six progressive PTCs. Key findings are corroborated through in vivo and in vitro experiments. Single‐cell RNA sequencing and spatial transcriptomics characterized the cellular ecosystem within PTC, revealing multi‐directional evolutionary patterns as PTMC progresses. Analysis of progression‐specific alterations in intercellular communication networks highlighted the PROS1‐MERTK signaling interaction as pivotal in PTMC progression. In vitro and in vivo models confirm that the PROS1‐MERTK axis accelerates PTMC progression via paracrine and autocrine signaling. Furthermore, NFYB and FOXP2 are identified as activators of PROS1 transcription in fibroblasts, promoting PTMC progression through the MERTK/WNT/TGF‐β signaling. These findings underscore the PROS1/MERTK axis as a critical component of the cellular microenvironment and a key regulatory mechanism in PTMC progression.